(untitled) (International Journal of Nursing Education, 2019)
Background: Ethics and legal training in nursing provides a foundation and point of reference for ethical and legal issues that nurses may encounter during the practice of nursing. Extant research has shown that, in the global context, nurses are the largest group of health care providers. They frequently have to make decisions about their patients. Adequate training on issues of ethics and law is essential. Purpose: The purpose of this study was to explore nurses’ views on the ethics and legal training that they receive from training schools, identify any gaps in curricula and suggest ways to ensure adequacy of the and legal content in the nursing curriculum. Method: A cross-sectional quantitative design was used in this study. Data were collected by means of a self-administered questionnaire which was developed, tested and disseminated to 150 nurses working in the six district hospitals of Ghana. Data analysis was by SPSS 25.0. Results: The majority of the nurses believed their training on both and legal issues to be inadequate and felt that some issues were not covered, such as being a witness in court and signing legal documents. Conclusion: Adequate training on and legal principles applicable to health care is paramount during the preparation of nurses.